Estudios de doctorado en enfermería en México: el impacto de la globalización - Salazar Barajas, Martha Elba; Benavides Torres, Raquel Alicia; Gallegos Cabriales, Esther Carlota (National League of Nursing, 2012)
A country's development is directly linked to the educational attainment of its people. In 2011, Mexico's basic educational level was extended from nine to 12 years of education (Secretaría de Gobernación, 2011). Access to and quality of basic education are foundational to undergraduate and graduate university education. According to the population census of 2010, of the children and youth (six to 14 years) who should attend elementary and middle education, 94.7 percent were enrolled in school. Of youth between 15 and 24 years, only 40.4 percent completed college (Instituto Nacional de Geografía e Informatica, 2010). The segment of the population with access to graduate studies in the country is much lower. Data from 2008-2009 show that nationwide enrollment in master's programs was 166,986 students, while in doctoral programs the enrollment was only 18,530 (Asociación Nacional de Universidades e Instituciones de Educación Superior, 2011).